Forme solide et École solide : comment penser une nouvelle grammaire (architecturale) scolaire ? - Béatrice Mabilon-Bonfils; Virginie Martin (Éducation et Socialisation, 2017)
The scholastic form is questioned on all sides by mutations which affect as much the way of thinking, organizing and dispensing knowledge as the social and political function a verticality of the solid school form answers to a liquid trans-modernity. This school is not yet affected by that the digital and global double turn. The knowledge-relation supposes a new grammar school opening to the extensive school.